2015
DOI: 10.1038/srep12775
|View full text |Cite
|
Sign up to set email alerts
|

MiR-210 inhibits NF-κB signaling pathway by targeting DR6 in osteoarthritis

Abstract: Osteoarthritis (OA) is characterized by degradation of articular cartilage and joint inflammation. MicroRNAs have been proved to play an important role in the regulation of chondrogenesis. Previous study showed that microRNA-210 (miR-210) was probably associated with osteoarthritis, while the function of miR-210 in osteoarthritis still remains unknown. The aim of the present study was to investigate the protective effect of miR-210 on osteoarthritis. In the in vitro study, miR-210 level in chondrocytes was dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 30 publications
5
76
0
Order By: Relevance
“…In contrast to the above results, our data indicated that suppression of miR-302b suppressed LPS-induced injury of the chondrocyte cells. Our study found that knockdown of miR-302b exerts a protective role in human OA chondrocytes, which was in line with a previous study [25]. …”
Section: Discussionsupporting
confidence: 81%
“…In contrast to the above results, our data indicated that suppression of miR-302b suppressed LPS-induced injury of the chondrocyte cells. Our study found that knockdown of miR-302b exerts a protective role in human OA chondrocytes, which was in line with a previous study [25]. …”
Section: Discussionsupporting
confidence: 81%
“…Another study by Zhang et al utilized both in vitro and in vivo approaches to show potential chondroprotective effects of miR-210 (158). Overexpression of miR-210 via mimics was found to inhibit lipopolysaccharide-induced proinflammatory cytokines and cell death in primary rat chondrocytes and that one of its potential targets was death receptor 6 (DR6) mRNA.…”
Section: Other Mirnas Associated With Inflammatory Pathways In Oamentioning
confidence: 99%
“…Members of the TNF receptor superfamily (TNFRSF) upon activation are important inducers of apoptosis [135]. Previous studies have shown that death receptor 6 (TNFRSF21) is upregulated in OA and is targeted by miR-210, which is downregulated in OA [136, 137]. Hypoxia inducible factor-1-α (HIF-1α) regulates chondrogenesis as well as apoptosis and autophagy in chondrocytes [138].…”
Section: Mirna Regulation Of Apoptosis and Autophagy In Oamentioning
confidence: 99%